Strategi Pengembangan Program Studi Al-Ahwal Asy-Sayksiyyah (AHS) Jurusan Syariah dan Ekonomi Islam STAIN Samarinda - Ashar, Ashar (FENOMENA, 2014)
The existence of al-ahwal asy-Sayksiyyah study program is a new hope in developing the human resources quality. Strengthening this study program needs an adequate infrastructure to fulfill all the needs of academic and non-academic tools to support the learning process in enriching the educational goals at the study program. This is a descriptive qualitative research design. This study wants to describe the strategy of developing al-ahwal asy-Sayksiyyah study program. The instruments used are observation, interview, and documentation. The data analyzed by using SWOT. The results of the study show that there are strength, weakness, opportunity, and the threat in developing al-ahwal asy-Sayksiyyah study program. The strategy implemented to develop al-ahwal asy-Sayksiyyah study program are: The socialization of vision, mission, goal, and the target of the study program, strengthen learning process, leadership, management, guality assurance, improvement of the alumnae quality, improvement of the staffs and lecturers, research development, society services, and MoU with other parties.